2017
DOI: 10.3892/etm.2017.5639
|View full text |Cite
|
Sign up to set email alerts
|

The role of Dexamethasone in clinical pharmaceutical treatment for patients with cataract surgery

Abstract: Abstract. The aim of the present study is to determine the efficacy of dexamethasone (DEX) vs. indomethacin (IND) and ciprofloxacin (CIP) in modulating immediate inflammation following cataract surgery. A total of 644 patients with cataract were recruited and inflammation was investigated during the perioperative period. The management protocol was similar in both groups. Each drug was given four times a day for 30 days starting 7 days prior to surgery. The primary efficacy criteria for evaluation were the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The study by Zhang et al demonstrated that the average inflammation score was significantly lower in Dexamethasone group compared with the Indomethacin and Ciprofloxacin groups. Moreover, they also witnessed decreased intra-ocular pressure with Dexamethasone compared to other study interventions 22 .…”
Section: Discussionmentioning
confidence: 85%
“…The study by Zhang et al demonstrated that the average inflammation score was significantly lower in Dexamethasone group compared with the Indomethacin and Ciprofloxacin groups. Moreover, they also witnessed decreased intra-ocular pressure with Dexamethasone compared to other study interventions 22 .…”
Section: Discussionmentioning
confidence: 85%
“…The present study describes a MSs formulation incorporating three established therapies with anti-inflammatory and neuroprotective activity; dexamethasone, melatonin and coenzyme Q10. The corticosteroid dexamethasone (DX) is commonly used in the treatment of ocular inflammation in conditions such as diabetic macular edema, central retinal vein occlusion, and uveitis [25][26][27]. Melatonin (MEL) is an antioxidant with free radical scavenging and neuroprotective activity mediated via multiple mechanisms including the inhibition of the mitochondrial transition pore, reducing NO-induced apoptosis or reducing excitotoxicity Ca 2+ overload [28][29][30][31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Currently, used drugs that have primary cataract as a side-effect might be the simplest cataract risk factors to investigate, due to the ease in which they can be added to culture media over a range of clinically relevant concentrations. For example, dexamethasone is routinely prescribed to treat a variety of disorders, such as rheumatoid arthritis [80], ocular inflammation [81], and post-surgical inflammation [82,83]. Notably, long-term use of dexamethasone has been associated with posterior subcapsular cataract [84,85,86].…”
Section: Defining Cataract Mechanisms With Ror1-expressing Lens Cementioning
confidence: 99%